Mason's Retreat - Tilghman, Christopher (London Chatto and Windus, 1966)
In 1936, Edward and Edith Mason return to America after a decade in England, with their two sons Simon and Sebastien. Their destination is an old family estate on the coast of Maryland, known as 'The Retreat'. They plan to revive it, and restore their own diminished fortune. But events take a very different turn
Keywords: World War (1939-1945) -- United States--Eastern Shore -- American fiction